Factors Affecting Disaster Preparedness, Response, and Recovery Using the Community Capitals Framework. Issue 5 (3rd September 2018) - Himes-Cornell, Amber; Ormond, Carlos; Hoelting, Kristin; Ban, Natalie C.; Zachary Koehn, J.; Allison, Edward H.; Larson, Eric C.; Monson, Daniel H.; Huntington, Henry P.; Okey, Thomas A.
Abstract: Disaster research often focuses on how and why communities are affected by a discrete extreme event. We used the community capitals framework to understand how community characteristics influence their preparedness, response to, and recovery from successive or multiple disasters using the 1964 Good Friday Earthquake and the 1989 Exxon Valdez Oil Spill as case studies. This study assesses community response to these disasters by reviewing published literature on impacts to create profiles for six communities and by identifying community capitals before and during these disasters, and throughout the long-term recovery. While the presence of rich natural capitals commonly contributed resources to pre-disaster planning and long-term recovery, restriction of resource access immediately following the disasters was detrimental to many communities. Communities with strong political, social, and financial capitals tended to fare better immediately following disasters, enabling longer-term processes of transformation or recovery. However, in some communities the oil spill undermined these capitals more than the earthquake and resulting tsunami. In understanding how use and reliance on community capitals can lead to varied recovery success from different kinds of disasters, these findings can help coastal managers and planners prepare for future disasters.